The Effect of Health Education About Toileting on Knowledge, Attitude and Independence Of Children Age School In Sdn Gedongtengen - Dewie Meidyani; Armenia Diah Sari; Atik Badi’ah (Gaster, 2022)
Health is a prosperous condition in the form of physical, mental and social health that is free from disease. An effort to improve health is the PHBS program. The lowest percentage was in the city of Yogyakarta, namely 59.97%. The bad PHBS comes from school children. The problem that arises in school children is not using latrines (toileting) properly. Children who do not toilet and then detained can cause the child to wet the bed (enuresis) or defecate in their pants. Objective: This study aims to determine the effect of health education on toileting on the knowledge, attitudes and independence of school age children. Method: This research method is a quantitative study with a pre-experimental design (one group pretestposttest). Data were collected by means of a questionnaire and analyzed by Wilcoxon. Results: The results of Wilcoxon analysis showed that the p-value of the knowledge variable was 0.000 and 0.000, the attitude variable was 0.000 and 0.000 and the independence variable was 0.027 and 0.006. Conclusion: The conclusion of this study is that there is an effect of health education on toileting on the knowledge, attitudes and independence of school-age children at SDN Gedongtengen Yogyakarta.